RFID smart shelf matching network and 3-D antenna design - Wang, Wei Xiao. (2010)
For an inventory management, in the context of library, a RFID smart shelf system is extremely useful for tracking of materials such as books, magazines, compact disks. To further enhance the cost efficiency and tracking accuracy of the smart shelf system, the project demonstrates the design and development of a matching network, multi close range tags antenna and bin antenna.